2021: ¿El inicio de la postpandemia? - Morales-Camacho, María Fernanda (2021)
In 2020 the world faced diverse and fast changes in the social, political, and economic arena because of the effects of COVID-19. Countries worldwide implemented different measures in order to stop the spread of the virus, for instance,  governments tried to stop people's mobility within their territory with lockdowns and the international borders were closed as well. All these measures had severe consequences for national economies and, as a result, with an impact on global economic growth. For example, in 2020, the global growth decreased -3,5%, the international trade exchange fell by 5,5%. and key economic activities for many countries such as tourism experienced a dramatic fall with a reduction close to 74% in the international arrivals; then 2020 became the worst recorded year in the history of tourism.